The Analysis of Criminal Liability of Military Members as Perpetrators of Premeditated Murder (Moord) against a Car Rental Owner - Fatimah Az-Zahra; Abdul Kholiq (Jurnal Daulat Hukum, 2025)
Premeditated murder is a grave criminal offense and is classified as a grave crime because it directly violates the constitutional right to life as one of the most fundamental and non-derogable human rights. This study aims to provide an in-depth analysis of the criminal liability of military personnel involved as perpetrators of premeditated murder, using a normative juridical method through a case approach and an examination of the court’s decision. The discussion focuses on the application of general criminal law provisions to active soldiers tried within the military court system, which has its own distinctive characteristics. The findings show that although the two defendants played different roles one carried out the shooting directly while the other issued the instruction both were considered to share a common will and awareness in committing the criminal act. The court determined that the elements of intent and premeditation were fulfilled, rendering both defendants equally responsible. The author argues that when viewed through the lens of criminal law doctrine, which emphasizes a calm and deliberate mental state as an indicator of premeditation, the defendants’ psychological condition, which was influenced by situational pressure, may give rise to different interpretations of this element. Nevertheless, the court’s decision affirms that military status does not exempt an offender from criminal liability and may even serve as an aggravating factor, as the conduct is deemed to undermine the discipline, honor, and integrity of the armed forces.